Venezuelan Forced Migration to Peru During Sociopolitical Crisis: an Analysis of Perceived Social Support and Emotion Regulation Strategies - Okumura Clark, Alvaro Jesús (2021)
While many studies have examined the impact of forced migration on Venezuelan migrants in Latin America, to date scholars have not examined the effect of certain coping mechanisms, namely social support and emotion regulation. Using data from 386 Venezuelan migrants living in Peru (M = 20.22 years, SD = 1.33, 46.4% women), we investigated whether perceived social support from three different sources (family, friends, and significant other) correlated with emotion regulation strategies (cognitive reappraisal and suppression) while controlling for the type of cohabitation and time of residence. The results (1) confirmed the originally proposed internal structure of the Multidimensional Perceived Social Support Scale and Emotion Regulation Questionnaire, showing reliability and validity even in a sample of migrants. Findings demonstrated that (2) perceived social support from family positively predicted cognitive reappraisal strategy when including friends and significant other as covariates; (3) Venezuelans who have resided longer in Peru compared to more recent migrants used cognitive reappraisal strategy at a higher rate despite perceiving low family social support; (4) Venezuelans who resided in Peru for a longer period of time reported higher suppression strategy use when having low significant other support; and (5) there were gender differences regarding cognitive reappraisal as a dependent variable. More specifically, in men, family was a better predictor than friend or significant other support, while among women, family and significant other had the biggest impact. These results demonstrate the importance of social support elements and time of residence on the healthy management of emotions under difficult circumstances, such as forced migration.